If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22x + 3 = 9 + 21x Reorder the terms: 3 + 22x = 9 + 21x Solving 3 + 22x = 9 + 21x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-21x' to each side of the equation. 3 + 22x + -21x = 9 + 21x + -21x Combine like terms: 22x + -21x = 1x 3 + 1x = 9 + 21x + -21x Combine like terms: 21x + -21x = 0 3 + 1x = 9 + 0 3 + 1x = 9 Add '-3' to each side of the equation. 3 + -3 + 1x = 9 + -3 Combine like terms: 3 + -3 = 0 0 + 1x = 9 + -3 1x = 9 + -3 Combine like terms: 9 + -3 = 6 1x = 6 Divide each side by '1'. x = 6 Simplifying x = 6
| 2=2j-4 | | 8(9x-5)=2(5x+6) | | 4.4r+48.004=7.8(.06r-1.82)-6.5r | | 5x+7=5x-9 | | 108=4(3-6k) | | (2x^2+4x-2)-(5x^2+6x+3)+(-2x^2-3x-5)= | | 4x-25=x+8 | | ((13x-35)+(5x-19)+(2x+14))=180 | | 5x-15+5x+25=180 | | X+8=4x-25 | | 4k^2+8k+2=0 | | 6y+12x=198 | | 2/8x-2/3=7/12 | | 9d^2-6d-3=0 | | -7(2n-3)= | | Ax^2-(2a-1)x+a-2=0 | | 5.5r+3.2r= | | 10x^2+40x-50= | | 7d-d+4d-6=32 | | x^2+79=95 | | 5x-7=-10x*8 | | 12x-5l=4 | | y=x+4z*8x+17y | | 6x+6(x+5)=114 | | ((x-7)+(x)+(2(x)-21))=180 | | 3(b-5)=-5(-1-b) | | 23b+3.8b= | | 3log[8](2x-5)=6 | | 252/u/u=7 | | 252/u/=7 | | y-6=5/8(x-3) | | 1b-15=5b-3 |